2018
DOI: 10.1186/s12882-018-0848-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor (nivolumab)-associated kidney injury and the importance of recognizing concomitant medications known to cause acute tubulointerstitial nephritis: a case report

Abstract: BackgroundAcute tubulointerstitial nephritis (ATIN) has been increasingly recognized as an important manifestation of kidney injury associated with the use of immune checkpoint inhibitors (anti-PD-1 and anti-CTLA-4). While the exact pathophysiology remains unknown, corticosteroids are the mainstay of management.Case presentationWe describe a 67-year-old man with stage IV non-small-cell lung cancer who developed kidney injury during treatment with the anti-PD-1 antibody nivolumab. A kidney biopsy showed ATIN wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
1
55
0
1
Order By: Relevance
“…One case was managed with PPI discontinuation only, without administration of corticosteroid, and nivolumab was continued for 8 months after discontinuation of PPI, indicating that PPI was the key drug causing AIN in this case. In a case report, lansoprazole‐induced AIN after administration of nivolumab and drug‐induced lymphocyte stimulation test for lansoprazole was proven to be positive 6. In our case, however, no culprit medication associated with AIN was administered, indicating that an endogenous antigen attacked the kidney.…”
Section: Discussionmentioning
confidence: 51%
“…One case was managed with PPI discontinuation only, without administration of corticosteroid, and nivolumab was continued for 8 months after discontinuation of PPI, indicating that PPI was the key drug causing AIN in this case. In a case report, lansoprazole‐induced AIN after administration of nivolumab and drug‐induced lymphocyte stimulation test for lansoprazole was proven to be positive 6. In our case, however, no culprit medication associated with AIN was administered, indicating that an endogenous antigen attacked the kidney.…”
Section: Discussionmentioning
confidence: 51%
“…The authors of that case also described the importance of recognizing concomitant medications causing AKI associated with PD-1 blockade by ICIs. In that case, the blockade of the intrinsic PD-1 signaling pathway by anti-PD-1 therapy possibly disrupted the patients' long-standing immunological tolerance against lansoprazole by modulating T-cell immunoreactivity [15]. Therefore, we should also consider the possibility of PPI-induced AKI triggered by nivolumab in our patient.…”
Section: Discussionmentioning
confidence: 97%
“…Renal biopsies show tubulointerstitial infiltrates and edema, with a predominance of CD3+ mononuclear T cells. Granulomas and eosinophils may be present, although they are neither sensitive nor specific for ICPI--associated ATIN 29,30,[32][33][34] . Cassol et al have identified a particular immunohistochemistry staining pattern for PD -L1 in inflammatory and tubular epithelial cells that seems to be only found in ICPI -induced ATIN 27 .…”
Section: Acute Tubulointerstitial Nephritismentioning
confidence: 95%
“…nonsteroidal anti -inflammatory drugs or proton pump inhibitors), could cause ATIN. The case presented by Koda et al is a good illustration, with a positive drug -induced lymphocyte stimulation test for lansoprazole alerting for the importance of recognizing medications known to cause ATIN 29 .…”
Section: Acute Tubulointerstitial Nephritismentioning
confidence: 96%